Fair Data: History and Present Context - Carballo-Garcia, Ana; Boté-Vericad, Juan-José (Central European Journal of Educational Research, 2022)
In this paper, we discuss FAIR Data, why it exists, and who it applies to. We further review the principles of FAIR data and how they are managed in research centers. We also discuss the types of problems that researchers encounter, and what an information professional can do to assist them. At present, the vast majority of centers subscribe to the FAIR principles. However, both center and researcher face the arduous task of understanding, managing, and implementing the model. They must know data formats and standards. For a correct description and to facilitate data retrieval and interoperability, they must know about different types of metadata schemas. They must know about digital preservation and specific aspects of knowledge and information management. In addition, there are also ethical issues, intellectual property, and cultural differences. All these controversies translate into extra workload for researchers, who only get a return in the form of citations. It is critical to note that these information professionals can play a key role in the proper management of research data, and can help achieve the objectives described in the principles: making data findable, accessible, interoperable, and reusable.